Standarisasi Pengintegrasian Undang-Undang Penghapusan Kekerasan Dalam Rumah Tangga di Pengadilan Agama - Zainullah, Achmad (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2014)
Standardization of integration of the law on the elimination of domestic violence in Religious Court is a correlation of the domestic violence with the Religious Court's authority as set forth in article 49 of Law No. 7 of 1989. It has already been accommodated in the applicable procedural law in Religious Court, both the act itself and the Guideline for its Implementation. Most cases of the domestic violence which are handled by Religious Court, are hidden in contested divorce cases. One of the reasons the wife asks for a divorce in general is economic neglect by her husband, an act, which,according to Law No. 23 of 2004 on the elimination of domestic violence, is a form of a pure domestic violence. Procedurally, the Religious Court institution is not a legal institution mandated to enforcement of this Act. However, the characters of the domestic violence cases are very in touch with family and become one of the triggers of divorce to be in the Religious Court’s judicial competence. So that, Religious Court is a part of the legal institution that has a strategic role in order to remove all types of the domestic violence. Religious court is the first door to reveal the domestic violence that was previously closed neatly. Therefore, although it is not directly prosecuting the criminal acts, Religious Court has a strategic role in revealing the domestic violence. [Standarisasi pengintegrasian Undang-Undang Penghapusan Kekerasan dalam Rumah Tangga (PKDRT) di Pengadilan Agama adalah adanya korelasi KDRT dengan kewenangan PA sebagaimana tertuang dalam pasal 49 UU Nomor 7 tahun 1989. Pengintegrasian UU PKDRT di Pengadilan Agama telah diakomodir dalam hukum acara yang berlaku di Pengadilan Agama, baik Undang-Undang maupun Pedoman Pelaksanaan Tugas. Kebanyakan kasus Kekerasan dalam Rumah Tangga yang ditangani oleh Pengadilan Agama ‟tersembunyi‟ dalam perkara cerai gugat. Salah satu alasan isteri meminta cerai pada umumnya adalah penelantaran ekonomi oleh suami, suatu tindakan yang menurut Undang-undang No. 23 Tahun 2004 tentang Penghapusan KDRT merupakan salah satu bentuk Kekerasan dalam Rumah Tangga. Secara prosedural, institusi peradilan agama bukanlah institusi hukum yang menerima mandat penegakan UU ini. Akan tetapi, karena karakter kasus KDRT sangat berhubungan dengan keluarga dan menjadi salah satu pemicu perceraian -perkara yang menjadi kompetensi peradilan agama- maka peradilan agama juga menjadi bagian institusi hukum yang memiliki peran strategis dalam rangka menghapus segala jenis kekerasan dalam rumah tangga, pengadilan agama adalah pintu pertama terkuaknya berbagai kekerasan dalam rumah tangga yang sebelumnya tertutup rapi. Karena itu, meskipun tidak langsung mengadili tindak pidananya, pengadilan agama memiliki peranan strategis dalam menguak peristiwa KDRT.]